The distributional effects of conventional monetary policy and quantitative easing: Evidence from an estimated DSGE model - Stefan Hohberger; Romanos Priftis; Lukas Vogel (Publications Office of the European Union, 2018)
This paper compares the distributional effects of conventional monetary policy and quantitative easing (QE) within an estimated open-economy DSGE model of the euro area. The model includes two groups of households: (i) wealthier households, who own financial assets and are able to smooth consumption over time, and (ii) poorer households, who only receive labor and transfer income and live "hand to mouth". We use the model to compare the impact of policy shocks on constructed measures of income and wealth inequality (net disposable income, net asset position, and relative per-capita income). Except for the short term, expansionary conventional policy and QE shocks tend to mitigate income and wealth inequality between the two population groups. In light of the coarse dichotomy of households that abstracts from richer income and wealth dynamics at the individual level, the analysis emphasizes the functional distribution of income.
Keywords: E44; E52; E53; F41; 330; Bayesian estimation; distributional effects; open-economy DSGE model; portfolio rebalancing; quantitative easing